2013 American Control Conference 2013
DOI: 10.1109/acc.2013.6580137
|View full text |Cite
|
Sign up to set email alerts
|

Finite-time coordination in multiagent systems using sliding mode control approach

Abstract: Finite-time stability in dynamical systems theory involves systems whose trajectories converge to an equilibrium state in finite time. In this paper, we use the notion of finitetime stability to apply it to the problem of coordinated motion in multiagent systems. Specifically, we consider a group of fully actuated agents described by Euler-Lagrange dynamics along with a leader agent with an objective to reach and maintain a desired formation characterized by steady-state distances between the neighboring agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 8 publications
0
44
0
Order By: Relevance
“…One of FTC methods is to use the sign function (see other works [17][18][19] ). The terminal sliding mode control is another FTC technique (see other works [20][21][22] ). However, both of them belong to the discontinuous control, which can cause jittering.…”
Section: Introductionmentioning
confidence: 99%
“…One of FTC methods is to use the sign function (see other works [17][18][19] ). The terminal sliding mode control is another FTC technique (see other works [20][21][22] ). However, both of them belong to the discontinuous control, which can cause jittering.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, through the analysis of the control scheme, it can be found that the prior TSM suffers from a singularity problem, that is, in some areas of the state space, the TSM control torque may require to be infinity large to maintain the ideal TSM motion . To avoid the singularity problem, a lot of effective methods were proposed, which can be broadly split into two classes, ie, direct method and switching method . For the direct method, the zero velocity states will decelerate and complicate the reaching phase even though they are not attractors.…”
Section: Introductionmentioning
confidence: 99%
“…7 To avoid the singularity problem, a lot of effective methods were proposed, which can be broadly split into two classes, ie, direct method 21,22 and switching method. [23][24][25][26][27] For the direct method, the zero velocity states will decelerate and complicate the reaching phase even though they are not attractors. Additionally, for the switching method, the system settling time will be extended with the switching motion between the LSM and the TSM.…”
Section: Introductionmentioning
confidence: 99%
“…Because the dynamics of many mechanical systems can be modeled as double integrators, the MAS with double‐integrator dynamics have gained great attention in recent years . Recently, MAS with general high‐dimensional linear dynamics have attracted much attention of researchers in the control field .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional sliding mode design methods fail to maintain stabilizations when facing mismatched uncertainties [16][17][18]. 2304 S. MONDAL, R. SU AND L. XIE Because the dynamics of many mechanical systems can be modeled as double integrators, the MAS with double-integrator dynamics have gained great attention in recent years [1,2,9]. Recently, MAS with general high-dimensional linear dynamics have attracted much attention of researchers in the control field [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%